VARIATIONS IN FREQUENCY AND AMPLITUDE OF NONSPECIFIC ELECTRODERMAL RESPONSES - Bari, Dindar S. (Science Journal of University of Zakho, 2024)
Electrodermal activity (EDA) represents changes in the electrical properties of the skin due to the opening of sweat pores and sweat secretion. EDA responses are classified into specific and nonspecific responses. Nonspecific EDA responses (NS.EDRs) are EDA responses without external stimuli or motor activity and are shown to be a good measure of psychophysiological states and traits. Studies investigating NSEDRs are rare, especially on responses, which occur following specific responses at resting periods. This study aimed to investigate variations in NS.EDRs  (in terms of frequency and amplitude) at a sequence of resting periods (pre and post of various stimuli). NS.EDRs parameters were recorded from 20 subjects simultaneously in the same skin area. They were computed at resting periods before and following specific responses due to five external stimuli. The study results indicated that there were differences in the frequency and amplitude of NS.EDRs recorded at different resting periods. Additionally, the frequency of NS.EDRs obtained before stimuli were more than those detected at other resting periods, whereas amplitudes of NS.EDRs following sound stimulus were higher than those computed before and after other stimuli; however, these results were statistically nonsignificant (p>0.05). This study suggests that nonspecific skin potential responses (NS.SPRs) are very sensitive to capture variations in the frequency and amplitude of NS.EDRs, whereas nonspecific skin susceptance responses (NS.SSRs) are the least sensitive compared to nonspecific skin conductance responses (NS.SCRs) and NS.SPRs. NS.EDRs may be an important indicator for tracking arousal, emotional behavior, psychophysiological variables, and goal-directed thinking in clinical applications due to their sensitivity to such responses.
Keywords: Amplitude; electrodermal activity; frequency; nonspecific responses; specific responses